2012
DOI: 10.1084/jem.20121072
|View full text |Cite
|
Sign up to set email alerts
|

The intramembrane protease Sppl2a is required for B cell and DC development and survival via cleavage of the invariant chain

Abstract: The protease Sppl2a cleaves the N-terminal fragment of invariant chain (CD74) and is required for efficient B cell development and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 29 publications
3
105
0
Order By: Relevance
“…Furthermore, functionality of the remaining B cells is considerably impaired with regard to Ig production. Major phenotypic findings described in this study were additionally confirmed in two SPPL2a mutant mouse lines (19,20). Additional ablation of CD74 in SPPL2a 2/2 mice improved B cell maturation and function, indicating that the B cell phenotype of these mice can be mainly ascribed to the incomplete turnover of the CD74 NTF (13).…”
supporting
confidence: 71%
“…Furthermore, functionality of the remaining B cells is considerably impaired with regard to Ig production. Major phenotypic findings described in this study were additionally confirmed in two SPPL2a mutant mouse lines (19,20). Additional ablation of CD74 in SPPL2a 2/2 mice improved B cell maturation and function, indicating that the B cell phenotype of these mice can be mainly ascribed to the incomplete turnover of the CD74 NTF (13).…”
supporting
confidence: 71%
“…Accumulation of the membrane-bound invariant chain fragment prevents proper B-cell development. Hence, SPPL2a inhibition might be a strategy to treat B cell-dependent autoimmune diseases [59,60].…”
Section: Aspartate Impsmentioning
confidence: 99%
“…This requires cathepsin S (Riese et al 1996;Driessen et al 1999;Nakagawa et al 1999;Shi et al 1999) or cathepsins L and F (Nakagawa et al 1998;Shi et al 2000), depending on the cell type. Degradation of the remaining transmembrane fragment requires the intramembrane endopeptidase SPPL2A (Beisner et al 2013;Bergmann et al 2013;Schneppenheim et al 2013). Although early studies proposed that Ii degradation is regulated and enhanced in response to DC activation (Pierre and Mellman 1998), subsequent studies proved that Ii processing is a constitutive process and not rate limiting for antigen presentation by MHCII (Villadangos et al 2001(Villadangos et al , 2005El-Sukkari et al 2003;ten Broeke et al 2010).…”
Section: Biosynthesis Of Mhciimentioning
confidence: 99%